The effects of octreotide in a patient with Nelson's syndrome. Issue 843 (January 1996) - Kelestimur, F.; Utas, C.; Ozbakir, O.; Selçuklu, A.; Kandemir, O.; Ozcan, N.
Abstract : We have administered octreotide, 100 micrograms tid, to a 27-year-old man with Nelson's syndrome. After seven days of therapy, adrenocorticotropin levels fell to 54% of initial values, and some shrinkage of the tumour was observed. This study indicates that octreotide therapy may have a role in the treatment of Nelson's syndrome.